OP29 A measure to improve assessment and management of symptoms and concerns of people with dementia in care homes: development and mixed methods evaluation. (September 2018) - Ellis-Smith, C; Higginson, IJ; Evans, CJ
Abstract : Background: Detection and management of physical symptoms and psychosocial concerns for people with dementia is essential to reduce suffering. Measures used in routine care can support assessment and change care processes to improve outcomes. We aimed to develop and conduct a feasibility and process evaluation of the mechanisms of action (MOA), acceptability and implementation requirements of the Integrated Palliative Care Outcome Scale for Dementia (IPOS-Dem) to improve comprehensive assessment and management of symptoms and concerns of residents with dementia in care homes. Methods: A mixed methods interventional design informed by the MRC framework and underpinned by a theoretical model of expected MOA. Study conducted in three care homes involving residents with dementia, family, care staff and health professionals. IPOS-Dem V1 was developed from the validated IPOS through a scoping review of symptoms and concerns common in dementia. Two sequential phases followed. Phase one comprised focus groups/semi-structured interviews and cognitive interviews to evaluate content validity, comprehensibility and acceptability; and refinements to IPOS-Dem made. Phase two employed an embedded mixed methods design to evaluate MOA, feasibility and implementation requirements. Residents received IPOS-Dem as part of routine care for 12 weeks. Qualitative data included focus groups, semi-structured interviews and observations. Quantitative data comprised IPOS-Dem scores. Directed content analysis and descriptive statistics was used for qualitative and quantitative data analysis respectively, analysed separately and then integrated on key areas to inform a final theoretical model. Results: Phase one: 26 family, care staff and health professionals participated in focus groups/interviews, and 10 care staff in cognitive interviews. Five additional items were identified as important for content validity. Refinements to improve acceptability and comprehensibility included use of lay terms and item descriptors. Phase two: 32 residents received IPOS-Dem and 18 family, care staff and health professionals participated in focus groups, interviews and observations. Key MOA were improved collaborative assessment resulting in improved detection of symptoms and concerns; comprehensive 'picture of the person' which supported systematic record-keeping and monitoring, and facilitated communication between care staff, family, and health professionals. IPOS-Dem was perceived as easy to use and providing value to care, with the proportion of missing data decreasing from 2.1% at baseline to 1.1% at 12 weeks. Conclusion: IPOS-Dem is an acceptable and feasible measure to improve comprehensive assessment and management of symptoms and concerns in residents with dementia. A theoretical model of likely MOA and implementation requirements is presented. Further psychometric testing and effectiveness trial is required. Funders: Cicely Saunders International, Atlantic Philanthropies. This research was supported by the National Institute for Health Research (NIHR) Collaboration for Leadership in Applied Health Research and Care South London (NIHR CLAHRC South London) at King's College Hospital NHS Foundation Trust. The views expressed in this article are those of the author(s)and not necessarily those of the NHS, the NIHR, or the Department of Health and Social Care.